Preoperative Oral Gabapentin in the Management of Postoperative Catheter-Related Bladder Discomfort in Adults: A Systematic Review and Meta-Analysis - Wang, Yu-Ting; Xiao, Chong; Liu, Hong; Fu, Xi; Ren, Yi-Feng; You, Feng-Ming (Frontiers in Surgery, 2021)
Objective: To evaluate the efficacy of preoperative oral gabapentin in preventing postoperative CRBD in surgical patients. Methods: Randomized controlled trials in which gabapentin was used for the prevention of CRBD in surgical patients with transurethral catheterization were evaluated. The primary outcome was the incidence of moderate-to-severe CRBD at 0, 1, 2, and 6 h after surgery, and secondary outcomes included the incidence of any grade CRBD, postoperative pain scores, and postoperative complications. Pooled risk ratios (RRs) and mean difference (MD), 95% confidence intervals (CIs), and P values were estimated using fixed and random effects statistical models. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to rate the levels of certainty for key results. Results: A total of 6 randomized controlled trials involving 679 participants were included in the meta-analysis. Gabapentin significantly reduced the risk of moderate-to-severe CRBD at 0, 1, 2, and 6 h (0 h: RR =0.19, 95% CI: 0.11 to 0.31, p < 0.00001; 1 h: RR =0.40, 95% CI: 0.25 to 0.66, p < 0.001; 2 h: RR =0.38, 95% CI: 0.26 to 0.56, p < 0.00001; 6 h: RR =0.20, 95% CI: 0.11 to 0.38, p < 0.00001). The overall incidence of CRBD at 1 h showed no statistical difference between the two groups (RR =0.55, 95% CI: 0.30 to 1.00, p = 0.05). The risk of CRBD was significantly reduced in the gabapentin group at 0, 2, and 6 h after surgery (0 h: RR =0.59, 95% CI: 0.46 to 0.74, p < 0.0001; 2 h: RR =0.62, 95% CI: 0.51 to 0.75, p < 0.00001; 6 h: RR =0.66, 95% CI: 0.52 to 0.83, p < 0.001). In addition, gabapentin was associated with low postoperative pain intensity, although it had no effect on other postoperative complications. Conclusion: Preoperative oral gabapentin as an adjunct to surgery is effective in decreasing the risk and severity of CRBD over a short time after surgery, and it can decrease postoperative pain but has no effect on other postoperative complications. Overall, the level of certainty was moderate to low.